Three Malay Theological (Aqida) Texts of the 19th Century and Issues Connected to Human Actions - Nasrin Nasir (Universitas Islam Negeri Mataram, 2021)
This paper attempts to provide an archeology of knowledge more specifically the knowledge of faith as it is taught in contemporary Malaysia. Several texts have been identified to be taught in various madrasahs and at times local community prayer halls called “surau” in teaching credal belief to the religious students and public. A total of three main texts had been identified as being the most popular in the teaching of credal belief to the masses. Credal belief as it is sanctioned by the country’s religious establishment is the Asha’irah school which is part of the broad Ahlussunnah wal Jamaah belief system in Islam. The texts chosen are the popular texts used in teaching aqidah in the madrasah and mosques in the country. They are al-Durr al-Thamin (1232/1817), Aqidatun Najin fi ilmi usul al-Din (1308/1891) and Faridatul Fara’id (1313/1895). The relation between God and His creatures as depicted in the texts here would be exposed and analysed. Whether human actions are free or taking from the teachings of Ash’arite theologians, the idea of kasb is explained. This paper via a critical textual analysis aims to ask questions connected to issues of freewill while highlighting the role of God in human actions.